2018
DOI: 10.1177/1060028018820625
|View full text |Cite
|
Sign up to set email alerts
|

Topical Tranexamic Acid for the Treatment of Acute Epistaxis: A Systematic Review and Meta-analysis

Abstract: Objective: To compare topical tranexamic acid (TXA) with control groups for the treatment of acute epistaxis assessing bleeding cessation, discharge within 2 hours, rebleeding rates, complication rates, and patient satisfaction. Data Sources: PubMed, CINAHL, LILACS, Scopus, the Cochrane Database of Systematic Reviews, and the Cochrane Central Register of Controlled Trials were searched from inception to November 2018. Study Selection and Data Extraction: All randomized controlled trials comparing topical TXA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…While the studies utilized different search strategies, both were informed by similar studies in their reviews. The current review further supports the potential value of this intervention …”
Section: Narrativesupporting
confidence: 67%
See 1 more Smart Citation
“…While the studies utilized different search strategies, both were informed by similar studies in their reviews. The current review further supports the potential value of this intervention …”
Section: Narrativesupporting
confidence: 67%
“…Another recent systematic review of topical TXA in epistaxis identified faster discharge rates, reduced rebleeding at 24 hours, and greater patient satisfaction with TXA, but no difference in rebleeding at 30 minutes . While the studies utilized different search strategies, both were informed by similar studies in their reviews.…”
Section: Narrativementioning
confidence: 99%
“…Another important goal is to determine the optimal dosage of tranexamic acid in treatment of anterior epistaxis. Recently, a systematic review was published by Gottlieb et al 16 Although it has been reported that pledgets soaked in 5 mL (500 mg) of tranexamic acid were used in most studies, a different dosage of tranexamic acid was used in other studies. 12,13 Overall, we believe that to define optimal dosage and the optimal method of using topical tranexamic acid, novel studies conducted with a standardized dosage regimen and method are required.…”
Section: Discussionmentioning
confidence: 99%
“…16 Use of topical tranexamic acid has been shown to reduce length of stay in emergency departments and decrease re-presentation rates, and it gives higher patient satisfaction rates than standard care. [25][26][27] Support for systemic tranexamic acid in epistaxis cases is more equivocal, but there is some evidence to support its use in select cases to reduce re-bleeding rates (e.g. in haemorrhagic telangiectasia), and there is no convincing evidence of adverse events when used for epistaxis.…”
Section: Epistaxismentioning
confidence: 99%